2014
DOI: 10.1590/1516-1439.267214
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of polypropylene/TiO2 nano-composites

Abstract: In this research, we have investigated the photocatalytic degradation of carbon-coated TiO 2 nanoparticles in polypropylene-based nano-composites. For this purpose, polypropylene-based nano-composites were prepared using carbon-coated TiO 2 nanoparticles and commercially available TiO 2 nanoparticles (Degussa, P25). Our results from SEM, FTIR, and tensile tests showed that the photocatalytic property of TiO 2 causes chain scission reactions, crosslinking and consequently photocatalytic degradation of polypropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The pressure and temperature was not altered to Mars levels since these tests were primarily to study the UV resistance of these new organic materials. formation, and physical deformation 16,29 . These phenomena were marginally noticeable in 24 h exposed samples and were in tandem with previously reported polymer degradation studies.…”
Section: Uv Chamber and Uv Radiation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure and temperature was not altered to Mars levels since these tests were primarily to study the UV resistance of these new organic materials. formation, and physical deformation 16,29 . These phenomena were marginally noticeable in 24 h exposed samples and were in tandem with previously reported polymer degradation studies.…”
Section: Uv Chamber and Uv Radiation Testmentioning
confidence: 99%
“…The Tg of the composite films was increased with the loading level of lignin nanohybrid because lignin-saponite hybrid had higher Tg than that of the PSBA copolymer (23.19 o C). The UV exposure time had slightly negative effects on the Tg of the composite films, which possibly indicated that the polymer matrix was degraded 29,32 . This is further corroborated by FTIR data, which shows that UV radiation results in the random scission of the polymer chain backbone 1,2,33 .…”
Section: The Effects Of Uv Radiation On the Thermal Properties Of Thementioning
confidence: 99%
“…TiO 2 is widely used as a model photocatalyst owing to its efficient oxidizing ability of organic pollutants ( Yuan et al., 2017 ). TiO 2 has performed exceptionally well in various studies for the removal of organic pollutants under UV light, and there is a need to further study its use for microplastic degradation, although few studies have used TiO 2 /plastic composite materials for the development of photodegradable plastic ( Kemp and McIntyre, 2006 ; Shang et al., 2003 ; Zan et al., 2006 ), such as polypropylene (PP) ( Kamrannejad et al., 2014 ), polystyrene (PS) ( Shang et al., 2003 ), and high- ( Wang et al., 2015 ) and low-density polyethylene (PE) films ( Thomas et al., 2013 ; Thomas and Sandhyarani, 2013 ). TiO 2 nanotubes showed enhanced removal of low-density PE under visible light ( Ali et al., 2016 ), whereas the activity of TiO 2 was improved using copper phthalocyanine ( Zhao et al., 2008 ), polypyrrole ( Li et al., 2010 ), multiwalled carbon nanotubes ( An et al., 2014 ) for PE removal, whereas iron phthalocyanine ( Fa et al., 2008 ) and ferric stearate ( Fa et al., 2013 ) were applied for photodegradable PS.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its inertness, it is commonly not biodegradable and resists microbial or enzymatic degradation. Titanium dioxide can be used to accelerate the photodegradation of synthetic polymers, resulting in the release of other components or additives in the polymer with subsequent transformation processes, releasing a various number of transformation products into the environment [25,26].…”
Section: Uv Radiation In Terms Of Photocatalysis or Photocatalytic Efmentioning
confidence: 99%